“Serbian land” in the Tărnovо inscription of John Asen II in the light of the political and geographical terminology of the time - Komatina Ivana; Komatina Predrag (Zbornik Radova Vizantološkog Instituta)
This study examines the notion of friendship depicted in the epistolary corpus of Euthymios Malakes who served as bishop of Neai Patrai during the second half of the twelfth century. His letters do not contain solely references to everyday problems, such as the difficulties that his diocesan floc had to encounter because of the hatred, the rapacity and the insatiable greed of state tax collectors, but they are also considered as vehicles for emotions towards his relationship with his friends and peers, either clerics or laymen. Therefore, the aim of the present article is to highlight Malakes’ view regarding the notion of friend and to shed light on how his theory on friendship was influenced by ancient Greek and Christian writings.